2021
DOI: 10.17755/esosder.910301
|View full text |Cite
|
Sign up to set email alerts
|

Merhamet Doyumu Ölçeği̇ni̇n Geli̇şti̇ri̇lmesi̇

Abstract: Merhamet doyumu kişinin merhametli eylemlerde bulunmaktan dolayı elde ettiği memnuniyet halidir. Bu çalışmanın amacı yetişkinlerin merhamet doyumlarını belirlemeye yönelik Merhamet Doyumu Ölçeği'nin geliştirilmesidir. Ölçeğin psikometrik özelliklerinin belirlenebilmesi için 504 yetişkinden veri toplanmıştır. Yapılan açımlayıcı faktör analizi sonucunda 12 madde tek bir faktör altında toplanmış ve bu tek faktörlü yapı toplam varyansın %56,14'ünü açıklamıştır. Elde edilen bu tek faktörlü yapı doğrulayıcı faktör a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
5
0
2
Order By: Relevance
“…Therefore, due to its suitability for the study design and high internal consistency coefficient, the Compassion Satisfaction Scale developed by Nas and Sak in 2021 was preferred. 19 The findings of this study revealed that the Türk Kızılay's personnel and volunteers scored an average of 23.78 ± 5.29 on the Psychological Hardiness Scale and an average of 49.91 ± 15.53 on the Compassion Satisfaction Scale. When considering the lowest possible scores that can be obtained from the scales and comparing this study with previous research conducted separately on psychological hardiness and compassion satisfaction, it has been observed that the rates of psychological hardiness and compassion satisfaction in our study were higher.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Therefore, due to its suitability for the study design and high internal consistency coefficient, the Compassion Satisfaction Scale developed by Nas and Sak in 2021 was preferred. 19 The findings of this study revealed that the Türk Kızılay's personnel and volunteers scored an average of 23.78 ± 5.29 on the Psychological Hardiness Scale and an average of 49.91 ± 15.53 on the Compassion Satisfaction Scale. When considering the lowest possible scores that can be obtained from the scales and comparing this study with previous research conducted separately on psychological hardiness and compassion satisfaction, it has been observed that the rates of psychological hardiness and compassion satisfaction in our study were higher.…”
Section: Discussionmentioning
confidence: 66%
“…The Compassion Satisfaction Scale, consisting of 12 items, was developed by Nas and Sak as a 1-dimensional scale to assess an individual’s compassion satisfaction. 19 The scale uses a 5-point Likert-type response format, ranging from 1 (strongly disagree) to 5 (strongly agree). Higher scores on the scale indicate higher levels of compassion satisfaction, while lower scores indicate lower levels of compassion satisfaction.…”
Section: Methodsmentioning
confidence: 99%
“…There are other concepts related to compassion fatigue, which is frequently encountered in people working in areas that directly serve people. The concepts of burnout, traumatic secondary stress, posttraumatic stress disorder, compassion satisfaction are the concepts associated with compassion fatigue (15,5,16,17). The scale used in the study has two subdimensions as secondary trauma and occupational burnout.…”
Section: Compassion Fatiguementioning
confidence: 99%
“…Bireylerin merhamet düzeylerinin belirlenebilmesi ise sadece geçerli ve güvenilir ölçme araçlarıyla sağlanabilir. Alanyazın incelendiğinde merhamet konusunda geliştirilen ölçeklerin (Neff, 2003a;Specher ve Fehr, 2005;Adams, Boscarino ve Figley, 2006;Hacker, 2008;Hwang, Plante ve Lackey, 2008;Stamm, 2010;Pommier, 2011;Raes, Pommier, Neff ve Van Gucht, 2011;Burnell ve Agan, 2013;Martins, Nicholas, Shaheen, Jones ve Norris, 2013;Chang, Fresco ve Green, 2014;Lown, Muncer ve Chadwick, 2015;Cho ve diğerleri, 2018;Nas ve Sak, 2021a;2021b) mevcut olduğu anlaşılmaktadır. Merhamet konusunda Türkiye'de yapılan ölçek çalışmalarının genel itibariyle uyarlama şeklinde gerçekleştirildiği anlaşılmaktadır.…”
Section: Introductionunclassified
“…; Goetz ve diğerleri, 2010; Peterson, 2017;Nas, 2020;2021;Nas, Sak ve Tanhan, 2021;Jazaieri, 2018; Jazaieri ve diğerleri, 2014; Sak ve diğerleri, 2021; Strauss ve diğerleri, 2016) ve merhamet konusunda geliştirilen ölçekler(Burnell ve Agan, 2013;Hacker, 2008; Hwang ve diğerleri, 2008;Nas ve Sak, 2021a;2021b;2021c;Neff, 2003a;Pommier, 2011; Raes ve diğerleri, 2011;Sprecher ve Fehr, 2005) incelenmiştir. Ayrıca merhametin temel özelliklerinden biri olarak kabul edilen(Gilbert, 2009a;2009b) empati ile ilgili ölçek çalışmalarına(Bora ve Baysan, 2009;Dinç Altun, Değerli, Çikrıkcı ve Kınık, 2018;Güzel, Sevi Tok ve Güney, 2019;Gıca, Büyükavşar, İyisoy ve Güleç, 2021;Topcu, Erdur-Baker ve Çapa-Aydın, 2010) bakılmıştır.…”
unclassified